Alternative splicing affects the subcellular localization of Drosha - Link, Steffen; Grund, Stefanie; Diederichs, Sven (Nucleic acids symposium series, 2016)
Abstract. The RNase III enzyme Drosha is a key factor in microRNA (miRNA) biogenesis and as such indispensable for cellular homeostasis and developmental proce
Gesehen am 27.05.2020